Energy security in the Malaysia-Thailand joint development area - Fatemeh Baradari; Zulkifli Mohd Nopiah; Mazlinawati Abdul Majid; Sabirin Ja’afar; Nor Aieni Mokhtar; Izyan Munirah Mohd Zaideen; Mohamad Rosni Othman; Mohd Zaideen (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Malaysia-Thailand Joint Development Area (MTJDA) Authority was legally formed in 1979 by a Memorandum of Understanding (MOU) and a 1990 Agreement on the Constitution and Other Matters of MTJDA between the Malaysian and Thai governments. The MOU’s main goal is to explore and exploit oil and gas resources in a contested maritime area. According to the agreement, the Joint Development Area (JDA) is located in the North Malay Basin, off the coast of Thailand. This was a bilateral agreement permitted by the UNCLOS. Since production began in 2005, the area has significantly aided Malaysia and Thailand’s economic and energy security. The goal of this research is to look into the issues and challenges in political and economic aspects that could affect the bilateral agreement once it expires in 2028. The perspectives of decision-makers, industry participants, and government officials were gathered through qualitative methods, which included secondary data and interviews. The results show that the Malaysia-Thailand Joint Development Area has been a close partnership for the past 40 years, and both countries should keep the agreement because the JDA is defined as joint efforts by Malaysia and Thailand to explore and exploit natural gas resources through enhanced bilateral diplomatic relations, as well as contribute to global economic growth. Under the current JDA, the emphasis is on strengthening bilateral diplomatic relations through cooperative cooperation. Because the current arrangements benefit both countries in terms of strengthening their partnership, Malaysia and Thailand should keep the agreement in place.